2005
DOI: 10.1152/ajpcell.00391.2004
|View full text |Cite
|
Sign up to set email alerts
|

Subsarcolemmal and intermyofibrillar mitochondria play distinct roles in regulating skeletal muscle fatty acid metabolism

Abstract: Skeletal muscle contains two populations of mitochondria that appear to be differentially affected by disease and exercise training. It remains unclear how these mitochondrial subpopulations contribute to fiber type-related and/or training-induced changes in fatty acid oxidation and regulation of carnitine palmitoyltransferase-1beta (CPT1beta), the enzyme that controls mitochondrial fatty acid uptake in skeletal muscle. To this end, we found that fatty acid oxidation rates were 8.9-fold higher in subsarcolemma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
127
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 52 publications
11
127
0
1
Order By: Relevance
“…However, selectively greater increases in palmitate oxidation in SS mitochondria (ϩ100%) compared with IMF mitochondria (ϩ46%) have been observed previously in muscles of endurance trained rats (66), in which PGC-1␣ was undoubtedly also increased. All other reports (12)(13)(14), except one (15), have found that the mRNA abundance of skeletal muscle CPTI, whose protein product is a key regulator of fatty acid oxidation, was not altered by PGC-1␣ overexpression.…”
Section: Pgc-1␣-induced Fatty Acid Oxidation-mentioning
confidence: 45%
See 2 more Smart Citations
“…However, selectively greater increases in palmitate oxidation in SS mitochondria (ϩ100%) compared with IMF mitochondria (ϩ46%) have been observed previously in muscles of endurance trained rats (66), in which PGC-1␣ was undoubtedly also increased. All other reports (12)(13)(14), except one (15), have found that the mRNA abundance of skeletal muscle CPTI, whose protein product is a key regulator of fatty acid oxidation, was not altered by PGC-1␣ overexpression.…”
Section: Pgc-1␣-induced Fatty Acid Oxidation-mentioning
confidence: 45%
“…In one study from our laboratory (69) and in several others by Muoio and co-workers (2,66,70), the rates of fatty acid oxidation have been shown to be greater in mitochondria obtained from red muscle than in mitochondria obtained from white muscle. These studies suggest that there are intrinsic differences in the capacities to oxidize fatty acids by red and white muscle mitochondria.…”
Section: Pgc-1␣-induced Fatty Acid Oxidation-mentioning
confidence: 90%
See 1 more Smart Citation
“…Activation of PPAR␦ (38) and overexpression of PGC-1␣ (36) upregulate fatty acid oxidation. Endurance-type training has also been shown to increase fatty acid oxidation in the vastus lateralis muscle of obese women (13) and in red and white gastrocnemius muscle of rats run on a treadmill for 10 wk (30). Additional studies demonstrate that the capacity to oxidize palmitate in skeletal muscle is significantly reduced with human obesity and negatively associated with body mass index (28).…”
Section: Discussionmentioning
confidence: 98%
“…Mitochondria are located either around the nuclei, this subgroup is called subsarcolemmal mitochondria, or nestled between myofibrils. These mitochondria are named intermyofibrillar and have distinct activity from subsarcolemmal ones (Koves et al, 2005;Mollica et al, 2006). Intermyofibrillar mitochondria are mainly dedicated to energy production for muscle fiber contraction.…”
Section: Basic Knowledge On Mitochondrial Functioningmentioning
confidence: 99%